2009
DOI: 10.1007/s10566-009-9072-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hurricane Exposure and Anxiety Sensitivity on Panic Symptoms

Abstract: Trauma exposure has been associated with panic symptoms in adult samples, but little is known about the relationship between trauma and panic in children. Anxiety sensitivity (AS), or the fear of anxiety-related bodily sensations, may help explain the relationship between trauma and panic. To examine relationships among trauma, anxiety sensitivity, and panic symptoms, data were collected from youth in the New Orleans area 5-8 months after Hurricane Katrina (N = 302) and again 17-18 months after the hurricane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Mental illness and post-traumatic stress (PTSD) following disasters is a burgeoning field (Acierno et al, 2007; Galea et al, 2007; Neria et al, 2007; Hensley-Maloney and Varela, 2009), particularly given the increase in severe storms in coastal U.S. PTSD is the condition most often measured (Norris and Elrod, 2006), with an incidence of 30–40% among direct victim (Galea et al, 2005). In the present study, “stress” and “anxiety” were self-identified, but only 13 % of shore respondents volunteered “stress” as a concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental illness and post-traumatic stress (PTSD) following disasters is a burgeoning field (Acierno et al, 2007; Galea et al, 2007; Neria et al, 2007; Hensley-Maloney and Varela, 2009), particularly given the increase in severe storms in coastal U.S. PTSD is the condition most often measured (Norris and Elrod, 2006), with an incidence of 30–40% among direct victim (Galea et al, 2005). In the present study, “stress” and “anxiety” were self-identified, but only 13 % of shore respondents volunteered “stress” as a concern.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to determine costs for different aspects of recovery and preparedness (Schoenbaum et al, 2013), leading to development of sound public policy (Fairbank and Gerrity, 2007). Numerous studies have focused on trauma (Neria et al, 2008; Hensley-Haloney and Varela, 2009), health risks and effects (Aciermo et al, 2007; Ruggiero et al, 2009; Barbeau et al, 2010), mold (Brandt et al, 2006), evacuation and relocation (Uscher-Pines, 2009), and risk communication (Reynolds and Seeger, 2005)…”
Section: Introductionmentioning
confidence: 99%
“…Although literature examining AS in terms of COVID-19-specific mental health factors, particularly among Latinx persons, is non-existent, past related work suggests that AS may partially explain (mediate) the relationship between stressful life events and anxiety symptoms (McLaughlin and Hatzenbuehler 2009 ). Additional work from past large-scale natural disasters, particularly hurricanes, suggests that AS is related to panic disorder symptoms over and above the variance accounted for by trauma exposure (Hensley-Maloney and Varela 2009 ), and AS amplifies the effects of trait anxiety on somatic symptom presentation (Hensley and Varela 2008 ). Prospective research following a school shooting found that AS was significant associated with anxiety and post-traumatic stress symptoms (Boffa et al 2016 ).…”
mentioning
confidence: 99%
“…In particular, previous research has documented that pre-hurricane trait anxiety and negative affect levels predict PTSD symptoms above and beyond exposure to the trauma (La Greca, Silverman, & Wasserstein, 1998;. Anxiety sensitivity is another trait that has been studied in relation to hurricane exposure and panic (Hensley-Maloney & Varela, 2009). The authors assessed youth at 5-8 months and 17-18 months post Katrina and found that while hurricane exposure and anxiety sensitivity did predict panic symptoms at the initial assessment, the association between exposure and panic was not significant when youth were assessed at 17-18 months post disaster.…”
Section: Ontogenic Influencesmentioning
confidence: 99%